The Sharia inquiry, religious practice and Muslim family law in Britain - Bano, Samia (Islam in the world focus, 2023)
Introduction / Samia Bano -- 1. Religious-only Marriages in England and Wales: Taking the Long View / Rebecca Probert -- 2. Women and Shari'a Law: The Impact of Soft Legal Pluralism in the UK / Elham Manea -- 3. Sharia Councils in the UK: Reform and Regulation / Dr Islam Uddin -- 4. Domestic Abuse: The Dichotomy of Choosing Between Informal and Formal Forum for Mediation, Arbitration and Justice / Naheed Ghauri -- 5. Sharia Councils and Muslim Family Law: Analysing the Parity Governance Model, the Sharia Inquiry and the role of the state/law relations / Samia Bano -- Index.